UKRAINE IN THE GUAM SYSTEM - PARAKHONSKIY, Boris (CENTRAL ASIA AND THE CAUCASUS, 2008)
Consolidation of GUAM. Aims and Tasks. A political consultative forum of four post-Soviet states (Georgia, Ukraine, Azerbaijan, and Moldova) was set up on 10 October 1997 in Strasbourg where their presidents attended a summit of the Council of Europe to discuss the Trea-ty on Conventional Armed Forces in Europe. The Strasbourg declaration signed by the four presidents registered the level of political rapprochement and practical cooperation inside the group and identical positions on the key international issues and processes unfolding in the post-Soviet expanse. They described their common aim as promotion of European stability and security based on respect for sovereignty, territorial integrity, inviolability of frontiers, democracy, the rule of law, and human rights.Two years later, on 24 April 1999, Uzbekistan joined the structure at the Washington summit of the Council of Euro-Atlantic Partnership; in 2005, it left it for a number of reasons. Between 1999 and 2005 the alliance was called GUUAM.Propelled by the shared economic and political interests of the five members, the new structure moved ahead at a fast pace. Indeed, the member states needed alternative routes for Caspian oil and the Euro-Asian transportation corridor; they were looking forward to closer cooperation with the European and Euro-Atlantic structures.The processes going on in each of the GUAM members are not free of national specifics, how-ever, there are many common features that underlay the shared interests:The similar transformation processes unfolding in the socioeconomic and political systems launched by the collapse of socialism and the Soviet regime and moving toward democracy;The search for new forms of civilizational and national identity, as well as their own state-hood models (not free from the danger of ethno-confessional conflicts);The newly independent states’ intensive involvement in the world economic processes and information flows, which calls for new foreign policy patterns;Regional consolidation stimulated by the geopolitical forces’ pronounced interest in its re-source and geostrategic potential and their intensive penetration into it in pursuance of their own interests. As a member of the newly born regional organization, Ukraine became actively involved in its consolidation for political and economic considerations of its own: Kiev badly needed diverse contacts and new forms of international cooperation to promote its influence in the Black Sea region.